Russia's Weaponized Migration: Analysing its Impact on Finnish-Russian Border Security - Kaczmarek Krzysztof (2024)
This study aims to understand the frameworks of Russia's hybrid maneuvers , specifically the strategic use of migration, on Finland's security, as well as that of the European Union (EU) and the North Atlantic Treaty Organization (NATO). The focus is on examining how migration is used by Russia as a geopolitical tool to influence the security landscape of these regions.